The Effect of Dexamethasone on Symptoms of Posttraumatic Stress Disorder and Depression After Cardiac Surgery and Intensive Care Admission: Longitudinal Follow-Up of a Randomized Controlled Trial. Issue 3 (March 2016) - Kok, Lotte; Hillegers, Manon H.; Veldhuijzen, Dieuwke S.; Cornelisse, Sandra; Nierich, Arno P.; van der Maaten, Joost M.; Rosseel, Peter M.; Hofland, Jan; Sep, Milou S.; Dieleman, Jan M.; Vinkers, Christiaan H.; Peelen, Linda M.; et al.
Abstract : Objective: Cardiac surgery and postoperative admission to the ICU may lead to posttraumatic stress disorder and depression. Perioperatively administered corticosteroids potentially alter the risk of development of these psychiatric conditions, by affecting the hypothalamic-pituitary-adrenal axis. However, findings of previous studies are inconsistent. We aimed to assess the effect of a single dose of dexamethasone compared with placebo on symptoms of posttraumatic stress disorder and depression and health-related quality of life after cardiac surgery and ICU admission. Design: Follow-up study of a randomized clinical trial. Setting: Five Dutch heart centers. Patients: Cardiac surgery patients ( n = 1, 244) who participated in the Dexamethasone for Cardiac Surgery trial. Interventions: A single intraoperative IV dose of dexamethasone or placebo was administered in a randomized, double-blind way. Measurements and Main Results: Symptoms of posttraumatic stress disorder, depression, and health-related quality of life were assessed with validated questionnaires 1.5 years after randomization. Data were available for 1, 125 patients (90.4%); of which 561 patients received dexamethasone and 564 patients received placebo. Overall, the prevalence of psychopathology was not influenced by dexamethasone. Posttraumatic stress disorder and depression were present in, respectively, 52 patients (9.3%) and 69 patients (12.3%) who received dexamethasone and in 66 patients (11.7%) and 78 patients (13.8%) who received placebo (posttraumatic stress disorder: odds ratio, 0.82; 95% CI, 0.55–1.20; p = 0.30; depression: odds ratio, 0.92; 95% CI, 0.64–1.31; p = 0.63). Subgroup analysis revealed a lower prevalence of posttraumatic stress disorder (odds ratio, 0.23; 95% CI, 0.07–0.72; p < 0.01) and depression (odds ratio, 0.29; 95% CI, 0.11–0.77; p < 0.01) in female patients after dexamethasone administration. Health-related quality of life did not differ between groups and was not associated with psychopathology. Conclusions: Overall, our findings suggest that exogenous administration of the glucocorticoid receptor agonist dexamethasone—compared with placebo—during cardiac surgery does not positively or negatively affect the prevalence of posttraumatic stress disorder and depression. However, in female patients, beneficial effects on the occurrence of posttraumatic stress disorder and depression may be present. Abstract : Supplemental Digital Content is available in the text.